2013
DOI: 10.7547/1030516
|View full text |Cite
|
Sign up to set email alerts
|

Footwear Interventions

Abstract: Footwear interventions, including shoe insoles and foot orthoses, have the capacity to enhance balance control and gait in older people. This review assessed the evidence for the effect of footwear interventions on static and dynamic balance performance and gait in older populations and explored proposed theories for underlying sensorimotor and mechanical mechanisms. We searched the Medline, EMBASE, CINAHL (the Cumulative Index to Nursing and Allied Health Literature), and AMED databases and conducted hand sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 42 publications
0
37
0
1
Order By: Relevance
“…Recently, the textured insoles have also been considered in improvement of sensation status of plantar surface [20] or ankle injuries [21]. The use of textured insoles is based on the assumption that it changes the discharge rate of the mechanical receptors [19,22,23]. In addition, based on the theory of sensory reweighting, enhancement of sending data via mechanoreceptors may somewhat offset the inadequacy of other sources of balance [21,24,25].…”
Section: Crossmarkmentioning
confidence: 99%
“…Recently, the textured insoles have also been considered in improvement of sensation status of plantar surface [20] or ankle injuries [21]. The use of textured insoles is based on the assumption that it changes the discharge rate of the mechanical receptors [19,22,23]. In addition, based on the theory of sensory reweighting, enhancement of sending data via mechanoreceptors may somewhat offset the inadequacy of other sources of balance [21,24,25].…”
Section: Crossmarkmentioning
confidence: 99%
“…[3] Foot problems may increase the risk of falls with cohort studies indicating a relationship between foot and ankle problems and risk of falling [4,5]. In addition, inappropriate footwear may also contribute to poor balance and an increased risk of falls [6]. A randomised controlled trial (RCT) among 305 community dwelling older people in Australia who had foot pain showed that there was a 36% statistically significant reduction in the rate of falls for people who had received a multifaceted podiatry intervention, comprising of foot and ankle exercises, foot orthoses, footwear advice, subsidy for new footwear, and a falls prevention booklet combined with routine podiatry care compared with those just receiving routine podiatry [7].…”
Section: Introductionmentioning
confidence: 99%
“…Foot and ankle devices, including shoe insoles and AFOs have been shown to alter standing balance, 12 gait kinetics and kinematics 12-14 in healthy young, 13 aging, 12 rheumatoid arthritic 15 and diabetic neuropathic 14 populations. While their mechanism of action remains unclear, current theories suggest that footwear interventions may bring about their effects by way of providing mechanical support, shock attenuation and alterations in sensorimotor control, or a combination of all.…”
Section: Introductionmentioning
confidence: 99%